Learning science by doing science 10 classic investigations reimagined to teach kids how science really works, grades 3-8 - Colburn, Alan 1961- (Thousand Oaks, California Corwin, 2017)
This witty book adapts classic investigations to help students in grades 3 through 8 truly think and act like scientists. Chapter by chapter, this accessible primer illustrates a "big idea" about the nature of science and offers clear links to the Next Generation Science Standards and its Science and Engineering Practices. You'll also find: A reader-friendly overview of the NGSS; guidance on adapting the activities to your grade level, including communicating instructions, facilitating discussions, and managing safety concerns, and, case studies of working scientists to highlight specifics about the science and engineering practices.--Source other than Library of Congress.
A Joint Publication with NSTA Press, National Science Teachers Association.
Includes bibliographical references (pages 179-180) and index.
Keywords: Science -- Study and teaching (Elementary) -- Methodology; Science -- Study and teaching (Middle school) -- Methodology